Peran Gates Foundation Dalam Mewujudkan Keamanan Kesehatan Di Indonesia Tahun 2023-2024 - Diansari Solihah Amini; Tanti Nurgiyanti; Yeyen Subandi; Yohanes Angie Kristiawan; Na’imullah Annahar; Siti Aisyiyah (LPPM Institut Pendidikan Nusantara Global, 2026)
Health is one of the fundamental rights of the people that must be facilitated by the state. In realizing adequate health conditions, Indonesia cooperates with various actors, both state and non-state. One of the actors that plays a role in promoting adequate health in Indonesia is the Gates Foundation. The Gates Foundation is a family philanthropic organization that operates in the fields of health, gender equality, global development, and education. Through cooperation between Indonesia and the Gates Foundation, this study examines the contributions of the Gates Foundation to the realization of health security in Indonesia. This research employs a descriptive qualitative method by utilizing secondary data collected from relevant literature and documents. Using the concepts of philanthropy and health security, the role of the Gates Foundation in Indonesia is manifested through research initiatives on telehealth, the digitalization of health services, the strengthening of health policies, tuberculosis genomic surveillance, and vaccine development, also monitoring of women's and children's health.